Can we scale Digital Twins of Nature-based Solutions for stormwater and transboundary water security projects?. Issue 4 (27th April 2022) - Brasil, José Artur Teixeira; de Macedo, Marina Batalini; de Oliveira, Thalita Raquel Pereira; Ghiglieno, Filippo Giovanni; de Souza, Vladimir Caramori Borges; Marinho e Silva, Gabriel; Gomes Júnior, Marcus Nóbrega; de Souza, Felipe Augusto Arguello; Mendiondo, Eduardo Mario
Abstract: Nature-based Solutions (NbS) are presented as an alternative and decentralized solutions with different application scales for problems addressed to urban expansion as water quality reduction and floods. The usage of control strategies and mathematical modeling techniques has shown promising results for optimizing hydraulic and water treatment processes. The Digital Twins (DT) as process integration technology are widely used in industry, and recently these technique usages in urban water systems are showing effective results in both management and planning. However, there is a lack of proper literature definition for DT applied to NbS, especially for stormwater and transboundary water security projects. Thus, this paper sought through a literature review to access the existing conceptual challenges and the DT definition as a framework, identify how the mathematical modeling reported in the literature can improve the DT development, and evaluate the potential benefits associated with the application of DT in NbS. HIGHLIGHTS: This review accessed Digital Twin (DT) applications to water-related structures and developed a technical framework to combine Nature-based Solutions (NbS) and DT techniques. The NbS DT development was divided into five different entities, which can be individually expanded and mutually connected. The technical aspects of each entity were accessed with the specifications to attend NbS techniques.